PENERAPAN TEKNOLOGI FORCE MOLTING PADA AYAM PETELUR AFKIR STUDI DI DESA MUKIRAN KECAMATAN KALIWUNGU KABUPATEN SEMARANG - Ali Mursyid Wahyu Mulyono; Ahimsa Kandi Sariri; Wisnu Tri Husodo (Caraka Tani: Journal of Sustainable Agriculture, 2008)
The study was aimed to prove the value-added of force molting technology on rejected laying-hen and improve the knowledge and skill of Mukiran village people about its technical assistance. The method of this study was training about force molting technology on rejected laying hen and laying hen management. Training took place for four months in the form of technican and practical lessons. Training was given to 19 people of Mukiran village, consisted of 8 countryside functionaries and 11 central figures, and the study objects were 86 week of age of rejected laying hens. The result of this study indicated that the knowing-level of force molting technology and laying hen management increased 90% and 73%. Egg production of the rejected laying chicken of equal to 52% and increase up to 70.8% pasca force molting technology implemented. Implementation of force molting technology on 100 birds of rejected laying hen required 6.1 million rupiah investment capital with the profit of effort 299.9 thousand rupiah per month. It is concluded that the implementation of force molting technology on rejected laying hen can improve the value added of production and financial parameters, so it improve the knowledge and skill of participant about its technical assistance.